Development of lipid-based colloidal nanocarriers for topical application of acyclovir - Silva, Juliana (2017)
Herpes infections are very frequent infectious diseases, especially in individuals whose immune system is weakened, causing manifestations in the central nervous system that leave severe squeals in about 80% of cases. There are several types of etiologic agents of herpes infections, the most famous being the Herpes Simplex Virus HSV 1 and 2. HSV 1 usually affects the face, lips, gums, palate, tongue and nasal mucosa and can spread to other parts of the body and HSV 2 reaches the genital area, affecting both men and women [1]. The most common current therapies to treat herpes infections are based on topical application of creams containing an antiviral agent, but whose effectiveness is limited due to low skin penetration of the active agent , thus requiring the application of about four or up to five times per day for improving the therapeutic effectiveness of the formulation [1]. For this reason , there is great interest in developing formulations based on the use of nanocarriers of active ingredients to promote more effective penetration through the skin and thus to reduce the frequency of application. Biophysical characterization of the most common drug used to treat herpes, acyclovir, also revealed some pharmacokinetic problems related with drug biodistribution accessed by determination of: (i) distribution coefficients in membrane/water systems by derivative spectrophotometry; (ii) binding constants of the drug to serum human albumin by fluorescence quenching, dynamic and electrophoretic light scattering and (iii) drug effect on membrane microviscosity accessed by dynamic light scattering. To overcome the biodistribution problems found for acyclovir, this work further proposes the development of nanostructured lipid carriers (NLC) and monoolein based colloidal carriers containing the anti-viral drug. Formulations were evaluated regarding their stability characteristics (size, polydispersity, surface potential and lipid phase transition properties), as well as, the drug encapsulation efficiency and their release profiles when in contact with the skin pH. Finally, after selecting the formulation with the best biophysical characteristics, it was included in a vehicle (hydrogel) for topical application and the effects of the formulation on the rheological characteristics of the vehicle were evaluated to optimize the formulation with improved galenic properties. After the incorporation of the nanocarriers in the hydrogel it has demonstrated a pseudoplastic behavior with thixotropy favoring its administration.